Defect-Oriented 2D Nanocomposites as Flexible Piezoelectric Nanogenerators: Encapsulation Effect. (8th July 2021) - Shukla, Pooja; Amutha, Subramani; Sen, Arijit
Abstract : Here we investigate an energy harvesting effect on various types of stress applied to the piezoelectric polymer-filler based thin films. A solvent casting technique was used to fabricate well-crystalline graphene-lead oxide/PVDF (GLP) nanocomposite 2D material. The structure, morphology, and functional composition of GLP were studied by various characterization techniques. As-synthesized GLP harbors the twin advantage of graphene and lead in the sense that it is not only highly capacitive in nature with 95% retention, but also exhibits enhanced electrical conductivity of 1 μ S cm −1 . The improved preparation method of GLP can thus make it suitable as an energy harvesting material in helping it display an output voltage of 16 V. From our electrostatic study of the device model, it is further apparent that GLP can demonstrate excellent breakdown strength of 650 V m −1 with relatively low dielectric losses.